Banking liberalization and corporate tax planning: Evidence from natural experiments - Chen, Shenglan; Ma, Hui; Teng, Haimeng; Wu, Qiang (Journal of Corporate Finance, 2022)
This paper investigates whether banking liberalization affects corporate tax planning by exploiting China's two interest rate deregulations as quasi-natural experiments. We find that firms reduce their level of tax avoidance following banking liberalization and that the identified effect is concentrated in firms with more bank borrowing after liberalization, firms located in non-financial centers, as well as non-SOE firms and firms with fewer political connections. In addition, we find that firms reduce their use of related party transactions and tax-related bribery after banking liberalization. Our results suggest that firms engage in less tax avoidance with more available/cheaper external financial resources and that, on average, the costs of engaging in tax avoidance are higher than the costs of borrowing from banks.